PENGARUH ASSET TERHADAP TRANSAKSI PIHAK-PIHAK YANG MEMPUNYAI HUBUNGAN ISTIMEWA DENGAN MANAJEMEN INVENTORY SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hasibuan, Lismawati (Institut Agama Islam Negeri Padangsidimpuan, 2017)
The purpose of this study is to know and analyze empirically the effect of assets on the transactions of parties who have a relationship simultaneously and partially. And knowing the effect of inventory management can moderate the relationship between Acid test ratio (ATR) and Return on total Asset (ROA) with the related parties. The population in this study is taken from manufacturing companies (industrial and chemical sector) listed on the Indonesia Stock Exchange during 2014-2015 as many as 130 companies. The method used is a purposive sample method where the company that kreteria is 46 companies. The results of simultaneous research ATR (X1) and ROA (X2) have no significant effect to the Transaction of Parties with Related Parties (Y) Manufacturing companies in Indonesia Stock Exchange period 2014 - 2015. Then partially ATR (X1) Transactions of related parties (Y), and ROA (X2) partially have a positive and significant effect on the transactions of related parties (Y). And Variable inventory management (ITO and TATO) are not moderating variables that affect (strengthen or weaken) the relationship between ATR and ROA on the transactions of related parties.